Mortality trends and years of potential life lost due to suicide in adolescents - Beatriz Catarina dos Santos de Oliveira; Ruth Ellery Lima Flores; Amanda Cristina de Souza Andrade; Roberta Mendes Abreu Silva; Katiene Rodrigues Menezes de Azevedo; Vanessa Moraes Bezerra (Universidade de São Paulo, 2024)
ABSTRACT OBJECTIVE To assess the trend in mortality rates and years of potential life lost (YPLL) due to suicide among adolescents in Northeast Brazil. METHODS This is an ecological time series study, with secondary data from 2011 to 2020 from the Mortality Information System for adolescents aged 10 to 19 years in the Northeast region of Brazil. Groups of causes from the 10th Revision of the International Classification of Diseases were included: X60-X84 (intentionally self-inflicted injuries), Y10-Y19 (poisoning of undetermined intent), and Y87 (sequelae of intentional self-harm). Mortality coefficients and frequency distribution by sociodemographic variables, place of occurrence, and method of suicide were estimates. YPLL were estimated by gender and age. Joinpoint regression analysis was used, and the annual percentage change (APC) was determined with 95% confidence intervals. RESULTS A total of 2,410 deaths were recorded, with a predominance of adolescents aged between 15 and 19, males, of mixed-race, low schooling, and home was the main place of occurrence. The trend in the death rate was increasing in the Northeast (APC: 3.6%; p = 0.001), in girls aged 10 to 14 (APC: 8.7%; p = 0.003), in boys aged 15 to 19 (APC: 4.6%; p = 0.002) and in Bahia (APC: 8.1%; p = 0.012). Hanging/strangulation was the main method adopted by both sexes. The YPLL due to suicide were 11,110 in 2011 and 14,960 in 2020. CONCLUSION The precociousness of suicide committed by girls and the increase in mortality among older adolescents are noteworthy, and specific preventive measures need to be adopted for these groups in order to reduce this preventable cause of death.